Modulation of glucan‐enzyme interactions by domain V in GTF‐SI from Streptococcus mutans. Issue 1 (18th November 2018) - Osorio, Manuel I.; Zúñiga, Matías A.; Mendoza, Fernanda; Jaña, Gonzalo A.; Jiménez, Verónica A.
Abstract: Glucansucrase GTF‐SI from Streptococcus mutans is a multidomain enzyme that catalyzes the synthesis of glucan polymers. Domain V locates 100 Å from the catalytic site and is required for an optimal activity. Nevertheless, the mechanism governing its functional role remains elusive. In this work, homology modeling and molecular dynamics simulations were employed to examine the effect of domain V in the structure and glucan‐binding ability of GTF‐SI in full and truncated enzyme models. Our results showed that domain V increases the flexibility of the α4′‐loop‐α4″ motif near the catalytic site resulting in a higher surface for glucan association, and modulates the orientation of a growing oligosaccharide (N=8‐23) in glucan‐enzyme complexes towards engaging in favorable contacts throughout the protein, whereas in the truncated model the glucan protrudes randomly from domain B towards the solvent. These results are valuable to increase understanding about the functional role of domain V in GH70 glucansucrases.